2023
DOI: 10.1159/000529662
|View full text |Cite
|
Sign up to set email alerts
|

Expert Report on Immune Thrombocytopenia: Current Diagnostics and Treatment – Recommendations from an Expert Group from Austria, Germany, and Switzerland

Abstract: no Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 135 publications
1
15
0
Order By: Relevance
“…60 The impact of menorrhagia on patients' QoL was assessed using data from seven studies and indicated that menorrhagia had a negative influence on a patients' QoL, particularly F I G U R E 1 Key aspects of patient education in bleeding and thrombotic risk. 9,16,83 patients with a low PC. 74 In the iWISH study on patient perception, menorrhagia was rated as one of the most severe symptoms of ITP by 83% of surveyed patients who experienced it at diagnosis and by 62%…”
Section: Itp and Women's Healthmentioning
confidence: 95%
See 2 more Smart Citations
“…60 The impact of menorrhagia on patients' QoL was assessed using data from seven studies and indicated that menorrhagia had a negative influence on a patients' QoL, particularly F I G U R E 1 Key aspects of patient education in bleeding and thrombotic risk. 9,16,83 patients with a low PC. 74 In the iWISH study on patient perception, menorrhagia was rated as one of the most severe symptoms of ITP by 83% of surveyed patients who experienced it at diagnosis and by 62%…”
Section: Itp and Women's Healthmentioning
confidence: 95%
“…13 This risk of thromboembolism is increased in the presence of certain patient characteristics, such as older age, certain ITP treatments and even aspects of the disease itself. [14][15][16] Thrombotic events will also require initiation of anticoagulant and/or antiplatelet therapy and this can be challenging in patients with low PC. This review will discuss the risks of both bleeding and thrombotic events in adult ITP patients, as well as the aspects of ITP that specifically impact on women's health and quality of life, which are of particular concern due to haemorrhagic and thrombotic complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Huge variations exist across national guidelines from the recommendation to not test systematically every ITP for ANA (e.g. the recent German, Austrian and Swiss expert guidelines), 3 to systematic dosage (e.g. 2017 French guidelines).…”
Section: Introductionmentioning
confidence: 99%
“…Introduction Immune thrombocytopenia (ITP) is a rare chronic disease, frequently accompanied by fatigue, which is an important comorbidity associated with this disease 1 . Patients experience difficulties to manage their daily activities and a reduction in their overall quality of life (QoL) 2 .…”
mentioning
confidence: 99%